Design and ranging performance of a low-profile UWB antenna for WBAN localization applications - Zaric, A. (2014)
A very compact low-profile 37.6 mm X 27 mm X 3.1 m mm unidirectional UWB antenna is proposed for wireless body area network (WBAN) localization applications by focusing on its ranging performance and impulse fidelity in time domain in addition to frequency domain characteristics. The antenna is immune to direct skin contact, and also demonstrates very good frequency and time domain properties in free space or at any distance to a body: reflection coefficient and radiation pattern resilience to body influence; flat transfer function amplitude and linear phase over the desired frequency band from 6 GHz to 9 GHz. Superior time domain performance is demonstrated in simulation and measurements with average impulse fidelity of 97% in both free space and when placed at 0 mm or 3 mm over the body. Off-body ranging measurements show accuracies of the order of 5 cm and achievable range higher than 5 m for almost all frontal directions (16 m being the maximum), with transmitting power complying with the international regulation.